Methods for preserving fertility in childhood cancer patients - L. V. Adamyan; E. V. Sibirskaya; L. G. Pivazyan; L. B. Obosyan; V. S. Ananyeva; A. A. Laevskaya (ABV-press, 2024)
Each year, more than 400,000 children and adolescents under the age of 18 are diagnosed with cancer. The most common nosologies in childhood are leukemia, lymphoma and brain tumors. The use of chemoradiotherapy as an antitumor treatment in these cases is associated with a high risk of gonadotoxicity. The preservation of fertility in children and adolescents during malignant tumor therapy is one of the key aspects of treatment. To date, there are many unresolved issues in this problem, affecting the preservation of both physical and psychological health of patients in adulthood. The main methods of maintaining the reproductive function in girls are cryopreservation of ovarian tissue or oocytes, ovarian autotransplantation, the use of assisted reproductive technologies, including the techniques of in vitro fertilization and in vitro oocyte maturation, oophoropexy and neoadjuvant cytoprotective pharmacotherapy. The choice of fertility preservation method depends on many factors: the overall condition of the child, the type of malignant disease, the age and sexual status of the patient, the capabilities of the medical center, as well as legal and financial aspects. Due to the lack of information on pediatric oncofertility, large-scale multicenter clinical trials involving children and adolescents are needed.